Experimental investigation of the Moment Bolted Coupler (MBT) with steel on the bond strength under different monotonic pull-out tests - Mohamad Nor, Mohamad Amir; Ahmad, Nursafarina; Mansor, Hazrina (Universitas Mercu Buana, 2025)
The bond strength between steel reinforcement bars and mechanical bolted couplers (MBT) is essential for the structural integrity of reinforced concrete structures. However, various pull-out test methods yield inconsistent results when assessing this bond strength. This research examines the impact of reinforcement bar diameter (12mm, 16mm, and 20mm) and three different pull-out test configurations (M1, M2, and M3) on the bond strength of MBT couplers. The M1 method, employing direct tensile loading and a standard clamp zone, consistently produced the highest bond strength values across all bar diameters. Its simplicity, reliability, and adherence to standardized procedures make it the preferred method for determining the maximum bond capacity of MBTs. While the M2 and M3 methods offer insights into coupler behavior under complex loading scenarios, they exhibit lower bond strength values compared to M1. The M1 pull-out test method is recommended as the primary method for evaluating the bond strength of MBT in practical applications, with M2 testing as a potential supplement for a more comprehensive understanding of coupler behavior.